2017
DOI: 10.4111/icu.2017.58.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node density predicts recurrence and death after inguinal lymph node dissection for penile cancer

Abstract: PurposeTo determine the impact of lymph node density (LND) on survival after inguinal lymph node dissection (ILND) for penile cancer.Materials and MethodsOur institutional penile cancer database was queried for patients who underwent ILND. Clinicopathologic characteristics including LND and total number of positive lymph nodes (LNs) were analyzed to determine impact on recurrence-free survival (RFS) and overall survival (OS). LND, or the percent of positive LN out of total LN, was calculated as a categorical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Lughezzani et al demonstrated that LND > 22% was a better predictor of DSS (HR, 4.58; p < .001) than TNM staging (HR, 2.57; p = .161) in their analysis of 81 patients of SCC penis 15 . Ball et al 16 analyzed 28 patients of SCC penis and reported that LND > 5% independently predicted recurrence‐free survival and OS. Although, LND as a predictor of survival was proved by these authors, there is a lack of consensus about the optimal threshold of LND for predicting survival.…”
Section: Discussionmentioning
confidence: 99%
“…Lughezzani et al demonstrated that LND > 22% was a better predictor of DSS (HR, 4.58; p < .001) than TNM staging (HR, 2.57; p = .161) in their analysis of 81 patients of SCC penis 15 . Ball et al 16 analyzed 28 patients of SCC penis and reported that LND > 5% independently predicted recurrence‐free survival and OS. Although, LND as a predictor of survival was proved by these authors, there is a lack of consensus about the optimal threshold of LND for predicting survival.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown LN counts ranging from eight to 16 as prognostic, although limited by low numbers of patients or by inherent limitations of national registries . Other studies have evaluated the role of LN density as more prognostic than the total number of positive LNs removed . Further investigation is warranted to evaluate the prognostic role of LN density and its diagnostic and therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…From the previous studies we have known that examined lymph node (ELN) count and lymph node density (LND) are the percentage of positive LNs, which have been used as a prognostic factor for other tumors, such as esophageal cancer, non-smallcell lung cancer and bladder cancer (2,(10)(11)(12)(13)(14). Unfortunately, these were rarely studied in PeCa.…”
Section: Introductionmentioning
confidence: 99%